CT und MRT der Leber: wann, was, warum? - Budjan, Johannes; Schönberg, Stefan; Attenberger, Ulrike (Der Radiologe, 2017)
The detection and differential diagnostic clarification of liver pathologies play an important role in almost all medical disciplines. Because of its superior soft tissue contrast, the availability of liver-specific contrast agents and functional techniques, magnetic resonance imaging (MRI) is the method of choice for the diagnostics of focal and diffuse liver pathologies. In addition to its superior detection and differentiation capabilities, MRI can provide prognostic information and enable early assessment of the therapy response for malignant liver lesions using functional techniques, especially diffusion imaging. Computed tomography (CT) is the imaging method of choice for the detection of traumatic liver injury. Despite the increasing availability of functional techniques in CT, MRI remains the overall modality of choice in liver imaging.